(untitled) (Research, Society and Development, 2022)
Introduction: The inclusion of the visually impaired in society and in sport through Five-a-side Football, so that the visually impaired can practice through accessibility, leisure and sports adapted to the theme, which need to be done by government officials. Helping to overcome obstacles, make dreams come true, achieve achievements and professional success. Objective: To describe the meaning and characteristics of five-a-side football as a tool for the social inclusion of the visually impaired in the context of complexity in sport and in today’s society. Methodology: A narrative review of the article’s theme was developed through a digital search of scientific materials in the Google and Schielo databases. From this, 14 materials were chosen and read, consisting of: 2 monographs, 3 websites, data from the Censo (2020), the Statute of Persons with Disabilities and 7 articles for the construction of the narrative review. Conclusion of the Study: Five-a-side football is a form of futsal adapted for the visually impaired. Originating between 1920 and 1950, played on a court, with a ball that has a bell. Each team is made up of 5 players, with 4 blind players on the line and 1 blindfolded goalkeeper with low vision. It is currently a B1 classification sport in the International Federation of Sports for the Blind and has been present in the Paralympics since the Athens games (2004). However, there is not a great dissemination of the modality by the media and society. In addition, it is not among the government’s public policy priorities.